Nuciferine Relaxes Tracheal Rings via the Blockade of VDLCC and NSCC Channels - Yang, Xiao; Yu, Meng-Fei; Lei, Jun; Peng, Yong-Bo; Zhao, Ping; Xue, Lu; Chen, Weiwei; Ma, Li-Qun; Liu, Qing-Hua; Shen, Jinhua (Planta Medica, 2018)
This study aimed to elucidate the mechanisms of nuciferine (a main aporphine alkaloid of lotus leaf extract), which can induce relaxation in contracted tracheal rings. Under Ca2+-free and 2 mM Ca2+ conditions, we found that nuciferine had no effect on the resting muscle tone of tracheal rings. In contrast, nuciferine relaxed high K+-contracted mouse tracheal rings in a dose-dependent manner and inhibited both Ca2+ influx and voltage-dependent L-type Ca2+ channel currents induced by high K+. Similarly, nuciferine also inhibited acetylcholine-induced contractions in mouse tracheal rings in a dose-dependent manner. Meanwhile, both acetylcholine-induced intracellular Ca2+ influx and whole-cell currents of nonselective cation channels were blocked by nuciferine. Together, the results indicate that nuciferine-induced relaxation in tracheal rings mainly occurred due to the inhibition of extracellular Ca2+ influx through the blockade of voltage-dependent L-type Ca2+ channels and/or nonselective cation channels. These results suggest that nuciferine has a therapeutic effect on respiratory diseases associated with the aberrant contraction of airway smooth muscles and/or bronchospasm.
Keywords: airway smooth muscle; asthma; Ca2+ influx; nuciferine; relaxation; voltage-dependent L-type Ca2+ channel